Promotion on the Employees Performance of Nusantara Card Universe Branch Makassar - Eko Priyono R; Otto R. Payangan; Hendragunawan, S.Thayf (Scientia Integritas Utama, 2023)
Competition in the business world is increasingly competitive, companies are required to have a strong identity in maintaining survival. Discussing performance, especially employees, is an important issue to be researched both in the organization. This is inseparable from the company's goals which expect continuous employee performance improvement to achieve superior company performance. What is the relationship between promotion to employee’s performance? There are still few researchers who explore this question. This study aims to analyze the level of influence of promotion on employee performance at the Nusantara Card Universe Makassar Branch. This type of research is a quantitative study using questionnaires as primary data collection. The population and sample in this study were all permanent employees of the Nusantara Card Universe Makassar Branch. Thus, the sample in this study is a census sampling or saturated sample. The results of the study show that promotion has a significant effect on employee performance. Promotion will motivate hard work and increase employee morale as well as support higher employee performance. By understanding the factors that influence post-promotion performance, organizations can take better actions in employee development and improve overall efficiency and productivity.